(untitled) (Ágora de Heterodoxias, 2017)
The mission of a clinical laboratory is to provide information of quality, which is used in clinical and public health contexts. This study reports an action-research supported of the logical framework methodology, carried out in Netlab, a private national reference clinical laboratory in Ecuador. A participatory situational diagnosis was applied, evidencing that the incidents related to samples reception in the pre-analytical area generated complaints from external clients, being the most frequent one’s errors in data of patients and request of tests. Strengthen the processes of the quality management system in the pre-analytical phase was established as the main objective. The intervening sample was the internal and external clients of Netlab. It was used the technique of direct observation, and as a data collection instrument, a specific form of internal and external source quality management system (claims). The intervention strategies were: training of managers of biological samples, application of standardized protocols for the correct identification of patients as well as the implementation of an automated system (bar-code), in four associated laboratories. The obtained results show that the intervention reduced the percentage of errors of entry to the laboratory computerized system, decreased incidents in incorrect patient data, and reduced identification errors of patients and their biological samples. These strategies are a key component in strengthening the safe and effective healthcare that currently requires the quality health management.